STUDENTS’ PERCEPTION TOWARDS THE ROLE OF ICE BREAKING ACTIVITIES IN LEARNING ENGLISH AT SENIOR HIGH SCHOOL - Naila Al Ghifarah; Ririn Pusparini (FKIP, Universitas Banten Jaya, 2023)
One of many factors that can influence students' feelings while learning English is a teacher's method or style of instruction that is not precise or monotonous. A fun and attractive learning environment can help students focus better and become more motivated to learn. Applying learning strategies suitable to students' conditions is one solution for increasing students'' motivation. For instance, the